Possible linkage between asymmetry of atmospheric meridional circulation and tropical cyclones in the Central Pacific during El Niño years. - Tao Li (Public Library of Science (PLoS), 2021)
The El Niño-Southern Oscillation is one of the most important drivers of climate change on Earth, and is characterised by warmer (El Niño) or colder (La Niña) ocean surface temperatures in the equatorial Pacific. Tropical cyclones (TCs) and meridional circulation are the most influential weather events and climate phenomena, respectively. However, the link between TCs and meridional circulation anomalies (MCA) during El Niño years is unclear. Therefore, we calculated the accumulated cyclone energy index of TCs and the mass stream function of MCA from 1980 to 2018. Our results showed that TCs were closely related to the asymmetry of the MCA in the Central Pacific during El Niño years. An updraft anomaly in the North Pacific was found, which affected the response of MCA to El Niño from May to October during El Niño years. Therefore, the MCA intensity difference between the North and South Pacific increased, and the asymmetry was strengthened. This phenomenon may be strengthened by the combined effects of the equatorial westerly wind, relative vorticity, and warm ocean surfaces, which are controlled by El Niño. The equatorial westerly wind produces positive shear north of the equator, which increases the relative vorticity. The increase in relative vorticity is accompanied by a monsoon trough, leading to increased precipitation and updrafts. The background of the relative vorticity, updraft, and monsoon trough may be conducive to the generation and development of TCs. Our results prove that the possible link between TCs and the asymmetry of the MCA during El Niño years is derived from the combined effect of the equatorial westerly wind, relative vorticity, and warm ocean surfaces, thus providing a partial explanation for the link between TCs and the MCA.